Walt Disney imagineering : a behind the dreams look at making MORE magic real - Malmberg, Melody; Imagineers (Group) (New York : Disney Editions, 2010)
Describes how Disneyland, Walt Disney World, Tokyo Disneyland, and Disneyland Paris were created.
'A welcome book.'
Includes fold-out pages which reveal other illustrations.
Includes bibliographical references (p. 187) and index.
Keywords: Walt Disney Company; Walt Disney Company -- History; Imagineers (Group) -- History; Amusement parks -- Design and construction